Creating an ongoing research capability in speech technology for two minority languages: experiences from the WISPR project - NI CHASAIDE, AILBHE (My University, 2005)
This paper reports on efforts to set up a research capability in speech technology for two minority languages (Welsh and Irish), where the focus is on ensuring that this capability will outlive the project that provided the initial impetus (the WISPR project). The existing situation at the start of the project is summarized, together with the challenges (setting up plant and equipment from scratch, training researchers in specialised skills). Some innovative strategies are examined: remote working by researchers with regular intensive on-site work weeks, and the use of Internet technology as a medium for collaborative work patterns. It is hoped that these experiences may be useful to researchers in other minority languages who wish to set up a similar research capability.
Proceedings of the 9th European Conference on Speech Communication and Technology
INTERSPEECH 2005
PUBLISHED
Lisbon
Keywords: Computer science